Education Financing Resilience Strategy in Muhammadiyah Elementary Schools - Dhiya'elhaq, Muhammad Ghossan Nazhif; Ika Maryani; Achadi Budi Santosa (Journal of Management Studies and Development, 2025)
School financing plays a crucial role in supporting the quality of education and requires effective management and governance. This study explores the financing resilience strategy of an elementary school with limited managerial and financial capacity, including the challenges it encounters and the solutions it applies. The data were collected using a qualitative descriptive approach through in-depth interviews and documentation. The primary data sources were the school principal and treasurer, with supporting documents as secondary sources. This research was conducted at Muhammadiyah Girikerto Elementary School, Sleman, Special Region of Yogyakarta. Data analysis involved data reduction, data display, and conclusion drawing. The results indicate that the school has implemented a comprehensive financing strategy encompassing planning, execution, and evaluation stages. Despite limited resources, the school has effectively addressed financing challenges, ensuring the continuity of teaching and learning activities. These findings underscore the importance of a robust financing resilience strategy in maintaining educational quality, particularly in developing schools with limited resources.